Approach to Manpower Planning April 1958 Manpower Studies-8 - Planning Commission (Planning Commission, 1958)
The 1958 Conference on Manpower Planning, organized by the Planning Commission of India, addressed the critical relationship between economic development and the availability of trained scientific and technical manpower. Discussions highlighted severe shortages of engineers and skilled personnel, emphasizing the need for long-term projections aligned with national production targets under the Five-Year Plans. The conference underscored the importance of expanding educational capacity, improving manpower quality, and coordinating efforts across government and educational institutions to ensure sustainable industrial and economic growth.
Planning Commission Perspective Planning Division
Planning Commission Perspective Planning Division
Keywords: Manpower Planning; Five-Year Plans; Scientific And Technical Manpower; Engineering Education; Economic Development; Planning Commission Of India; Skill Shortages; Industrial Growth; Human Resource Projection; National Development Strategy